The Interaction of Corporate Governance, Growth, and Profitability on Earnings Quality: Firm Size as a Moderator - Haji, Sapto; Adwimurti, Yudhistira; Rahmani, Hani Fitria; Sudrajat, Ayi Mohamad (Jurnal EMT KITA, 2025)
Earnings quality is a critical aspect of financial reporting that garners significant attention from investors and other stakeholders. This study aims to examine the effects of corporate governance, growth, and profitability on earnings quality, with a focus on the moderating role of company size. The research targets cyclic and non-cyclic companies listed on the Indonesia Stock Exchange (IDX) in 2023. Employing a quantitative approach with a cross-sectional design, data from 180 companies (90 cyclic and 90 non-cyclic) were analyzed. The study utilized moderated regression analysis with SPSS version 26. The findings indicate that corporate governance, growth, and profitability have a significant positive impact on earnings quality. Company size significantly moderates the relationship between corporate governance and profitability with earnings quality but does not significantly moderate the relationship between growth and earnings quality. Moreover, no significant differences were identified between cyclic and non-cyclic companies regarding factors affecting earnings quality. These results reinforce the applicability of Agency Theory and Signal Theory in understanding earnings quality within the Indonesian capital market. The findings highlight the necessity of enhancing corporate governance frameworks and emphasizing sustainable growth and profitability to improve earnings quality. This study contributes substantially to the body of literature on earnings quality in emerging markets and lays the groundwork for future research in this domain.